MAQÄ€á¹¢Iá¸Œ SHARÄªâ€™AH SEBAGAI METODE PENGGALIAN HUKUM ISLAM: ANTARA AL-GHAZÄ€LÄª, AL-SHAá¹¬IBÄª, DAN AL-á¹¬ÅªFÄª - Thahir, A. Halil (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2016)
Islam comes to bring goodness to mankind. In practice Islamic law must deal with new issues that demand new legal solutions as well. It is often that a partial legal approach produces partial legal products by altering the welfare that is at the heart of Islamic SharÃ„Â«Ã¢â‚¬â„¢ah. The maqÃ„ÂÃ¡Â¹Â£id al-sharÃ„Â«Ã¢â‚¬â„¢ah approach can be a way for the development of Islamic law which is oriented towards human welfare so that Islam as raÃ¡Â¸Â¥matan lil-Ã¢â‚¬ËœÃ„ÂlamÃ„Â«n can really be realized. This article seeks to examine the development of the concept of maqÃ„ÂÃ¡Â¹Â£id al-sharÃ„Â«Ã¢â‚¬â„¢ah by emphasizing the characteristic of the three main figures of different schools of thought: al-GhazÃ„ÂlÃ„Â«, al-ShaÃ¡Â¹ÂibÃ„Â«, al-Ã¡Â¹Â¬Ã…Â«fÃ„Â«. Keywords: MaqÃ„ÂÃ¡Â¹Â£id al-SharÃ„Â«Ã¢â‚¬â„¢ah, MaÃ¡Â¹Â£laÃ¡Â¸Â¥ah, Islamic Law